Manajemen Pendidikan Anak Usia Dini Pada PAUD Bintang Rabbani Pekanbaru - Suharni Suharni, M.Pd. (Jurnal Ilmiah POTENSIA, 2019)
This study aims to describe the management of early childhood education at Bintang Rabbani ECD. This study uses a qualitative approach and is descriptive. The selection of research subjects was carried out using a purposive sampling technique. Research subjects are managers, educators, students, and parents. Data is collected through observation, interviews, and documentation. Checking the validity of the data is done through diligence of observation, participation, and adequacy of references. The results of the study indicate that the Bintang Rabbani PAUD program management was prepared in accordance with the vision and mission of the institution by implementing management functions including; planning, implementation, supervision and guidance. Managers as leaders in carrying out management functions strongly emphasize cooperation based on sincerity, enthusiasm, and high loyalty. Planning is done with strategic planning, preparation of learning plans ranging from annual, semester, monthly, weekly to daily. Organizing is done by coordinating tasks, opportunities, experiences and insights with open communication, holding regular meetings that discuss efforts to improve performance. Supervision is carried out by direct observation, through supervision, regular meetings with educators. Collaboration is done with parents, through monthly meetings (parenting), and partners related to PAUD. Assessment and evaluation are carried out by giving assignments, observations, diaries, anecdotes, performance, work results, and educational visits.